2010
DOI: 10.1007/s10508-010-9617-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Coercion Victimization and Perpetration in Heterosexual Couples: A Dyadic Investigation

Abstract: Sexual coercion (SC), or making another person engage in sexual activity despite his or her unwillingness to do so, has been shown to have negative consequences for victims, namely depression, anxiety, low self-esteem, and a negative view of one's sexual self. The goals of the present study were to investigate the rate of SC victimization and perpetration, inter-partner agreement concerning its occurrence, in addition to its degree of reciprocity within a sample of 222 heterosexual couples. SC within previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 39 publications
3
39
1
Order By: Relevance
“…Specifically, the most common forms of less severe sexual coercion include psychological manipulation and attempts at sexual arousal through insistent physical touching (Brousseau et al, 2011;Struckman-Johnson, Struckman-Johnson, & Anderson, 2003). Psychological manipulation is aimed at altering a person's cognitive or affective states and can include the making of false promises, threatening to spread unflattering rumors, threatening to end the relationship, or inciting a sense of guilt in one's partner (Brousseau et al, 2011;Struckman-Johnson et al, 2003). These psychological tactics are manipulative, in that they are intended to wear down the victim's resistance, or to deceive and trick the victim into engaging in sexual activity (Struckman-Johnson et al, 2003).…”
Section: Sexual Coercion: Less Severe Formsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, the most common forms of less severe sexual coercion include psychological manipulation and attempts at sexual arousal through insistent physical touching (Brousseau et al, 2011;Struckman-Johnson, Struckman-Johnson, & Anderson, 2003). Psychological manipulation is aimed at altering a person's cognitive or affective states and can include the making of false promises, threatening to spread unflattering rumors, threatening to end the relationship, or inciting a sense of guilt in one's partner (Brousseau et al, 2011;Struckman-Johnson et al, 2003). These psychological tactics are manipulative, in that they are intended to wear down the victim's resistance, or to deceive and trick the victim into engaging in sexual activity (Struckman-Johnson et al, 2003).…”
Section: Sexual Coercion: Less Severe Formsmentioning
confidence: 99%
“…In the broadest sense, sexual coercion can be viewed as a continuum of verbal and non-verbal behavior in which an individual is either induced or forced to engage in sexual activity (Spitzberg & Rhea, 1999). As a function of this broad definition, the term sexual coercion can include explicit and illicit acts, namely, rape, sexual abuse, sexual assault, and sexual harassment (Brousseau, Bergeron, Hébert, & McDuff, 2011). The conceptualization of sexual coercion, however, includes far more than these highly explicit and criminal acts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 13% of men and 5% of women used alcohol as a tactic, by taking advantage of an intoxicated person or by purposely intoxicating someone in order to obtain sex; 5% of men and 3% of women used forceful tactics. A Canadian study among 222 heterosexual couples showed that 17.1% of women reported having engaged in sexually coercive behaviour in their current relationship and 20.5% reported having sexually coerced a previous partner (Brousseau, Bergeron, Hébert, & McDuff, 2011). Low agreement between the reports of both partners suggests that this perpetration of sexual coercion was underreported.…”
Section: Coercive Strategiesmentioning
confidence: 99%